Consciousness and Cognition. The Cognitive Phenomenology Debate - Sacchi, Elisabetta; Voltolini, Alberto (Phenomenology and Mind, 2017)
According to a position which has dominated the theoretical landscape in the philosophy of mind until recently, only sensory states exhibit a characteristic phenomenal dimension, whereas cognitive states either utterly lack it, or inherit it from some of their accompanying sensory states. This position has recently been challenged by several scholars who have stressed the irreducibility of cognitive phenomenology to a merely sensory one. The aim of this introductory paper is to provide a general overview of the debate on cognitive phenomenology in order to give the reader a flavor of the richness of the themes that surround this area of investigation centered on the relationship between consciousness and cognition.